The Lagging Behind of Indian Education System (Global Journal of Human-Social Science, 2017)
Education enables the humans to achieve their fullest mental and physical potential in both personal and social life The importance of education cannot be overemphasized Education participates critically in building individual endowments and abilities it drives social and economic development at the national level India with more than a billion residents has the second largest education system in the world after China As of the beginning of 2017 according to experts estimates 29 7 of the population of India has been in the age group 0-15 years But counter to the image of India as a youthful engine of economic growth where many citizens work in some of the best technology centered jobs in the world HRD ministry statistics demonstrate a significant decline in national primary school enrollments If India s population is not trained to face the globalized world we will soon become a nation of servants clerks The below Article is about the defects in our present system of Education Read it mindfully for learning why a radical change is the need of the hour